Identification and expression analysis of sugar transporter family genes reveal the role of ZmSTP2 and ZmSTP20 in maize disease resistance - Yu-xin MA; Zhi-jun ZHOU; Hong-zhe CAO; Fan ZHOU; He-long SI; Jin-ping ZANG; Ji-hong XING; Kang ZHANG; Jin-gao DONG (Journal of Integrative Agriculture, 2023)
Sugar is an indispensable source of energy for plant growth and development, and it requires the participation of sugar transporter proteins (STPs) for crossing the hydrophobic barrier in plants. Here, we systematically identified the genes encoding sugar transporters in the genome of maize (Zea mays L.), analyzed their expression patterns under different conditions, and determined their functions in disease resistance. The results showed that the mazie sugar transporter family contained 24 members, all of which were predicted to be distributed on the cell membrane and had a highly conserved transmembrane transport domain. The tissue-specific expression of the maize sugar transporter genes was analyzed, and the expression level of these genes was found to be significantly different in different tissues. The analysis of biotic and abiotic stress data showed that the expression levels of the sugar transporter genes changed significantly under different stress factors. The expression levels of ZmSTP2 and ZmSTP20 continued to increase following Fusarium graminearum infection. By performing disease resistance analysis of zmstp2 and zmstp20 mutants, we found that after inoculation with Cochliobolus carbonum, Setosphaeria turcica, Cochliobolus heterostrophus, and F. graminearum, the lesion area of the mutants was significantly higher than that of the wild-type B73 plant. In this study, the genes encoding sugar transporters in maize were systematically identified and analyzed at the whole genome level. The expression patterns of the sugar transporter-encoding genes in different tissues of maize and under biotic and abiotic stresses were revealed, which laid an important theoretical foundation for further elucidation of their functions.